The Process-centered school : sustaining a renaissance community - Costa, Arthur L.;Liebmann, Rosemarie M. (Thousand Oaks, California : Corwin Press, 1997)
The Process-Centered School details the changes that must take place in order to shift from a traditional school system to a true learning organization. With process-centered education you will create efficient, lifelong learners by placing the focus on the learning process instead of content. This is the third book of a trilogy by the editors on process-centered learning. The first, Envisioning Process as Content, shows what learning is like when the learning process instead of content is the focus of curriculum. The second, Supporting the Spirit of Learning, examines how the role of the teacher changes in a process-centered school. This third volume offers suggestions and strategies for schools ready for a process-oriented learning environment. The focus of learning expands from within the school out into the community and institutions that support the classroom, including teacher preparation programs and the central office. Written for school administrators, teachers, staff developers, curriculum staff, and students and faculty of teacher preparation programs, The Process-Centered School will show you how to address the curriculum needs of the 21st century.
1. Constructing the metaphors for process -- 2. Spreading the good word : communicating with the school community to support change -- 3. Organizational learning : the essential journey -- 4. Designing learning for a new work environment : key values and skills -- 5. Staff development : a process approach -- 6. Preparing new teachers : process as curriculum -- 7. Developing adaptive schools in a quantum universe -- 8. The norms of collaboration : attaining communicative competence -- 9. The process of coaching : mediating growth toward holonomy -- 10. Developing a scoring rubric for a process school -- 11. Capturing the spirit : process pervades the organization -- 12. Searching for evidence : toward a renaissance community -- 13. Change : the journey begins -- 14. The essence : process as content.
Includes index.
Keywords: CURRICULUM PLANNING